Stalks and roots are the main battlefield for the coevolution between maize and Fusarium verticillioides - Xiong, Hao; Xing, Xiaobin; Liu, Muyuan; Zhang, Zhaoyu; Wang, Qingjun; Zhang, Xuemei; Gou, Xiangjian; Lu, Yanli; Feng, Xuanjun (Frontiers in Plant Science, 2024)
Fusarium species are the dominant cause of maize ear rot, but they also inflict serious damage to the roots and stalks. Theoretically, the organ where the host interacts with the pathogen most frequently should exhibit the highest degree of symptom-genotype correlation. Because that symptom-genotype correlation is an indicator reflecting the degree of coevolution between pathogen and its hosts. We wonder which organ is the main battlefield for the antagonism between maize and Fusarium. For this purpose, 43 isolates of Fusarium were isolated from infected maize ears. Fusarium verticillioides and F. graminearum are the two dominant pathogens, accounting for 44% and 30%, respectively. Furthermore, 14 elite maize inbreds were exposed to 43 Fusarium isolates and the symptoms of ear rot, stalk rot and root rot were investigated. In general, symptoms caused by F. graminearum were significantly more severe than those caused by other Fusarium species. Surprisingly, the genotype of F. verticillioides showed a strong correlation with stalk and root rot, but not with ear rot.Accordingly, our study may provide the first evidence that the stalk and root of maize, rather than the ear, is the main battlefield for the coevolution between maize and F. verticillioides.